Polar Transportation Equipment--Four-Wheel-Drive Vehicle with High-Flotation Tires. - Beard, W. H. (1969)
A four-wheel-drive vehicle with a V-8 engine, automatic transmission, 11:00 x 15 bar-tread, high-flotation tires, and a panel delivery body was tested over improved roads on abutting areas of snow, ice and frozen ground at McMurdo Station, Antarctica, for a 2-year period between Deep Freeze 67 and 69. It was used to haul light cargo and passengers both summer and winter in all kinds of weather, including temperatures to -50F. It was driven with ease by numerous drivers with varying degrees of winter driving experience on both smooth and rough roads, through snowdrifts up to 2 feet deep, and up 20% grades covered with patches of ice. Only minor maintenance and repairs were required in 15,000 miles of operation. During Deep Freeze 68, a four-wheel-drive vehicle similar to the test vehicle except for a station wagon body was adopted by the Naval Support Forces, Antarctica, as a command vehicle for McMurdo Station. The vehicle with either body configuration is recommended for inclusion in the equipment allowance list for a polar coastal station where fast comfortable transportation is essential for effective operation. (Author)